The Efectiveness of Booklet for Improved Knowledge and Attitude about Cigarette and its Dangerous at SDN 01 Panjang Selatan, Panjang, Bandar Lampung - Pakpahan, Patrick Ramos; Larasati, TA; Sibuea, Sahab; Sahli, Zamahsyari (Majority, 2014)
WHO reported that more than 6 million people die because of smoking behavior. Indonesia has been ranked 2nd for highest number of smoker. This behavior has already widespread in society, including elementary school teenagers. Smoking behavior in teenager associated with their knowledge, attitude at smoke and health education. Booklet as a media is one of health education media. This research has been done by using quasy-experimental approach method with non-randomized control group pretest-posttest design plan, consisting of 39 people in experimental group and 40 people from SDN 1 Srengsem as control group. The sampling technique that used is purposive sampling. Sample in this research are student of 6th grade with knowledge pretest score <10. Instrument used in this research are booklet and questionnaires. Mann–Whitney statistic result with α=0,05 shows that application of booklet is effective in increasing student’s knowledge past intervention (p=0,001) and three days after intervention (p=0,001) . Independent samples t–test result with α=0,05 shows that booklet ineffective in increasing student’s attitude both in past intervention (p=0,313) and three days after intervention with booklet (p=0,682) about cigarette and its dangerous at SDN 01 Panjang Selatan. Keywords : Attitude, booklet, cigarettes, health education, knowledge